(untitled) (Semiárida, 2025)
In the Lower Río Negro Valley (VIRN), during the 1960s, soil surveys were carried out that made it possible to characterize and group soils according to similarities in their components (texture, drainage, parent material, geomorphology, among others), taking into account the different profile horizons. These surveys resulted in the delineation of 15 soil mapping units of the soil-association type, represented in printed maps at a scale of 1:75,000, which are locally referred to as “soil series”. This information provided the technical basis for irrigation planning by the Lower Valley Development Institute (IDEVI). However, current access to these materials is limited due to their physical format and the partial loss of some original documents. In this context, the aim of this work was to digitize, georeference, and integrate the historical soil maps from IDEVI and their extension towards the coastal area into a unified Geographic Information System (GIS), covering a total area of 42,071 ha, using the open-source software QGIS. The main outputs include raster and vector products; unified soil maps, zoning based on soil attributes within the GIS environment, the recovery of previously lost information, and the reworking of the historical cartography for its visualization al scales of 1:120,000 (irrigated valley) and 1:200,000 (integrated valley-coast area), with cartographic layouts of adecuate readability and scalability. These products not only preserve a valuable technical legacy, but also provide updated tools to support research, outreach, and sustainable land management decisions in the region.